High-energy ball milling and hot pressing of the Ni-48Ti-2Sn and Ni-45Ti-5Sn powder mixtures - Kayano, Leandro Koji [UNESP] (2014)
This work presents the results on the high-energy ball milling and hot pressing of Ni- 48Ti-2Sn and Ni-45Ti-5Sn (at-%) powder mixtures. The milling process was performed in a planetary ball mill using stainless steel vial (225 mL) and hardened steel balls (19 mm diameter), rotary speed of 300 rpm, and a ball-to-powder weight ratio of 10:1. Samples were collected into the vial after different milling times: 60, 180 and 300 min. In the sequence, wet milling (isopropyl alcohol) was adopted up to 720 min in order to increase the powder yield into the vials. The asmilled and hot-pressed samples were characterized by X-ray diffraction, electron scanning microscopy, and energy dispersive spectrometry. Results indicated that the ductile particles were promptly cold-welded during the initial milling times. XRD patterns of the Ni-48Ti-2Sn powder mixture indicated that the peaks of Ni, Ti and Sn disappeared after milling for 3h. Following, peaks of NiTi and Ni4Ti3were preferentially formed during milling of Ni-Ti-Sn powders. A large amount of fine powders was yielded into the vial after wet milling for 720 min only. No significant carbon or oxygen contamination was detected by EDS analysis. Hot pressing produced homogeneous and dense samples which presented microstructures containing a large amount of the NiTi compound.